Electronics Cookbook : Practical electronic recipes with Arduino and Raspberry Pi - Monk, Simon (2017)
Arduino and Raspberry Pi have brought many new people to the world of electronics, particularly artists, hobbyists and designers who aren't trained in electrical engineering. If you're among them, don't fret. Rather than run out and get an EE degree, just pick up this handy cookbook whenever you need to solve a problem on your project.
Includes index.
Keywords: Arduino (Programmable controller); Raspberry Pi (Computer); Electronics; Technology